Artificial Intelligence Adoption, Employee motivation, competency and productivity enhancement in Human Resources - Andi Sumangelipu; Muh. Hasbi Abbas (Mandalika Institute, 2026)
Artificial Intelligence (AI) has emerged as a transformative technology reshaping Human Resource Management (HRM) by influencing workforce management, employee development, and organizational performance. Despite the growing body of literature, previous studies have largely examined AI adoption, employee motivation, competency development, and productivity enhancement independently, resulting in fragmented theoretical understanding. This study aims to synthesize contemporary literature on the relationships among these constructs within HRM. Employing a qualitative library research approach, the study systematically reviewed peer-reviewed publications published between 2024 and 2026, selected through predefined inclusion criteria focusing on AI applications in HRM and analyzed using qualitative content and thematic analysis. The findings indicate that AI adoption improves decision-making, automates routine tasks, supports personalized learning, and enhances workforce management effectiveness. AI also strengthens employee motivation by creating more meaningful work experiences while fostering competency development through continuous learning, upskilling, and reskilling, ultimately contributing to higher productivity and organizational effectiveness. Human–AI Collaboration is identified as a critical mechanism for integrating technological capabilities with human potential. The primary contribution of this study is the development of an integrated conceptual framework that explains how AI adoption simultaneously influences employee motivation, competency development, and productivity enhancement through a human-centered Human–AI Collaboration perspective, thereby addressing fragmentation in the existing HRM literature. The findings highlight the importance of human-centered AI implementation for achieving sustainable workforce performance and long-term organizational success.